Impact of age and comorbidities on real-world outcomes in advanced breast cancer patients treated with palbociclib in first line: a nation-wide Danish retrospective study - Alan Celik; Laurits Sebastian Dahl; Rasmus Garly; Vesna Glavicic; Maja Bendtsen Sharma; Sophie Yammeni; Humma Khan; Daniel Sloth Hauberg; Hanne Schultz Kapel; Ann Knoop; Tobias Berg (Acta Oncologica)
Background and purpose: Palbociclib, a cyclin-dependent kinase 4/6 (CDK4/6) inhibitor, combined with aromatase inhibitors (AI), can be used in first-line treatment for estrogen receptor (ER) positive, human epidermal growth factor receptor 2 (HER2) normal advanced breast cancer (ABC). This study aims to assess the impact of age and comorbidities on the progression-free survival (PFS) and overall survival (OS) of patients treated with palbociclib and AI.